The Causal Effect of the Dollar on Trade - Sai Ma; Tim Schmidt-Eisenlohr; Shaojun Zhang (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper establishes a causal link between the dollar exchange rate and international trade flows, employing a new instrument for the U.S. Dollar that is based on domestic U.S. housing activity (Ma and Zhang (2019)). In line with the dominant currency paradigm (Gopinath et al. (2020)), import prices and quantities respond strongly to a country's exchange rate with the U.S. dollar. Once we instrument the dollar, we find evidence for perfect pass-through of the dollar exchange rate to import prices. A dollar appreciation of 1 percent lowers import quantities by 1.5 percent for countries that fully invoice in dollars.
Keywords: F14; F31; G15; 330; dominant currency; dollar invoicing; international trade